Management of Nonformal Islamic Education Institutions: A Case Study Analysis on Majelis Taklim - Barus, Muhammad Irsan; Asari, Hasan; Arsyad, Junaidi (Fitrah: Journal of Islamic Education, 2025)
The governance of majelis taklim (Islamic study groups) is still diverse and unstandardized, resulting in differences in community participation and management effectiveness, which in turn affect the quality of Nonformal Islamic education. This study examines the governance of Nonformal Islamic educational institutions, specifically majelis taklim, through a qualitative multisite approach in eighteen majelis taklim in Mandailing Natal Regency. Data were collected through observation, interviews, and documentation. The results revealed two distinct governance models: open and closed. Open governance is typically found in majelis taklim established and managed by the community, characterized by high participation in decision-making and management. In contrast, closed governance is observed in majelis taklim managed by religious scholars, where decisions are centralized. The type of governance structure influences community participation levels, open governance shows higher involvement, while closed governance is more limited. These findings indicate that governance structures play a crucial role in determining community engagement and influencing Nonformal Islamic education practices. This study implies the importance of adaptive and participatory governance guidelines to enhance the effectiveness of Islamic study group management and strengthen the role of communities in Islamic education.